THE HYGIENICS OF TRANSLATION AND INTERPRETING: METAPHORS OF PURITY AND CONTAMINATION, AND THE CONSTRUCTION OF TRANSLATOR AND INTERPRETER IDENTITY - TORRESI, Ira (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The Hygienics of Translation and Interpreting: Metaphors of Purity and Contamination, and the Construction of Translator and Interpreter identity. Rooted in Critical Discourse Analysis and Pragmatics, and using metaphors as a heuristic tool, this essay will look at public and academic discourses on the practices of translation and interpreting associated with notions of cleanliness/purity vs uncleanliness/contamination. Such discourses may appear abstract and speculative in nature but have a practical impact on normative (self) perceptions of translators’ and interpreters’ professional behaviour and habitus. They also seem to run through the academic and theoretical understandings of translation and interpreting along the axes of fidelity/infidelity and translator’s invisibility/visibility, but also, by extension, in terms of respecting/trespassing boundaries (notions of norms of translation, or the interpreter as a conduit or gatekeeper). Real-life examples will be discussed to illustrate and deconstruct such metaphorical devices and highlight their connection with underlying value judgements attached to purity vs contamination. Existing metaphorical alternatives, which allow for the construction of more nuanced translators’/interpreters’ identities, will also be discussed. Igiena traducerii și a interpretării: metaforele purității și ale contaminării și construcția identității traducătorului și interpretului. Bazându-se pe instrumentele analizei critice a discursului și ale pragmaticii și folosind metaforele ca instrument euristic, prezentul articol va analiza discursurile publice și academice privind practicile de traducere și interpretare asociate cu noțiunile de curățenie/puritate vs. necurățenie/contaminare. Astfel de discursuri pot părea abstracte și speculative prin natura lor, dar au un impact practic asupra percepțiilor normative (de sine stătătoare) ale comportamentului și habitusului profesional al traducătorilor și interpreților. De asemenea, ele par să direcționeze abordările academice și teoretice ale traducerii și interpretării de-a lungul axelor fidelitate/infidelitate și invizibilitate/vizibilitate a traducătorului, dar și, prin extensie, în ceea ce privește respectarea/traversarea granițelor (noțiunile de norme de traducere sau interpretul ca un conducător sau gardian). Vor fi discutate exemple din viața reală pentru a ilustra și deconstrui astfel de dispozitive metaforice și pentru a evidenția legătura acestora cu judecățile de valoare implicite despre puritate vs. contaminare. De asemenea, vor fi discutate alternativele metaforice existente, care permit construirea unor identități mai nuanțate ale traducătorilor/interpreților. Cuvinte-cheie: metafore ale interpretării și traducerii, metafora conductei, metafora vasului, invizibilitatea traducătorului/interpretului, traducere “curată” Article history: Received 01 March 2024; Revised 09 June 2024; Accepted 01 September 2024; Available online 30 September 2024; Available print 30 September 2024.